The contribution of locked screw-plate fixation with varying angle configurations to stability of osteoporotic fractures: An experimental study - Bekler, Halil İbrahim; Bulut, Güven; Usta, Metin; Gökçe, Alper; Okyar, Ali Fethi; Beyzadeoglu, Tahsin Beyza (My University, 2008)
Objectives: This experimental study was designed to find new ways of improving stabilization of fractures in osteoporotic elderly patients through alterations made in the configuration and geometry of locked screw-plate fixation used in the conventional plate technique. Methods: Four screw configurations with varying angulations were used for plate-bone construction. Forty iron plates of high quality (100×35×3 mm) were divided into four groups and two screw holes, 3 mm in diameter, were drilled on each plate at a distance of 15 mm. In group A, the holes were drilled so that the screws would be vertically sent to the bone interface. In the remaining groups, the holes were drilled for convergent (group B, 15°) and divergent (group C, 15°; group D, 30°) screw orientation. Screw-plate fixation was tested in a modified osteoporotic bone (Osteoporotic Generic Bone, Synbone) on an Instron materials testing system with an axial pullout force of 0.1 mm/sec. Failure loads were read from load-displacement curves and the type of failure was noted. Results: Screws placed in divergent orientations showed the highest axial pull-out strength (group C, 83.3 N/mm; group D, 80.8 N/mm), followed by convergent placement (72N/mm) and vertical placement (66.7 N/ mm). The type of failure was breakage of the bone sample in divergent configurations, and screw pull-out in convergent and vertical configurations. Conclusion: Divergent constructs may be a promising alternative to conventional screw placement in treating osteoporotic fractures. ©2008 Turkish Association of Orthopaedics and Traumatology. © 2009 Elsevier B.V., All rights reserved.
Keywords: Biomechanics; Bone plates; Bone screws; Fracture fixation, internal/methods; Osteoporosis; Prosthesis design; Stress, mechanical